ChemInform Abstract: Ring‐Closing Enyne Metathesis of Terminal Alkynes with Propargylic Hindrance. Issue 40 (October 2015) - Laroche, Benjamin; Detraz, Morgane; Blond, Alain; Dubost, Lionel; Mailliet, Patrick; Nay, Bastien
Abstract The title reaction is investigated in the presence of different Grubbs catalysts.